Feasibility of a new V-shaped incision for parotidectomy: a preliminary report. Issue 5 (June 2018) - Ahn, D.; Sohn, J.H.; Lee, G.J.
Abstract: We report the design of a new V-shaped incision for parotidectomy that involves only preauricular and postauricular incisions and no hairline or upper cervical incision. It can be used to approach almost all the superficial parotid region, including the superior and anterior divisions, with minimal scarring. To evaluate its technical feasibility, safety, and cosmetic results, we prospectively enrolled 15 patients (between September 2015 and September 2016) who had partial parotidectomy as the primary treatment for benign parotid tumours. Operations were successfully completed through this approach alone in 14 (mean (range) operating time: 120 (105–142) minutes; drainage volume: 51 (23–70) ml; and duration of drainage: 2.6 (2–4) days). There were no serious complications such as paralysis of the facial nerve or necrosis of the wound. The mean (range) visual analogue scale (VAS) and Vancouver Scar Scale scores for the scars were 9 (8–10) and 0.9 (0–3), respectively. A V-shaped incision for partial parotidectomy is technically feasible and safe, and can produce good cosmetic results in selected patients with benign parotid tumours. Our results need to be confirmed in larger studies and case-control trials.